Alternative system to compute Rao diversity and dissimilarity coefficients with enhanced GUI and spreadsheet loading data input - Ibabao, Excelsa May N. (2010)
The quantification of ecological diversity is necessary in the practice of environmental planning and protection. Rao's quadratic entropy quantifies ecological diversity. It is the only diversity index reflecting both species difference and abundance. The species difference values may be generated using Izsak and Papp's(1995) method which takes into account the taxonomic data of the species. In the ade4 package of R, the functions for generating the taxonomic distances, and for computing DIVC and DISC already exist. However, R's method of input is through command lines. This make it high prone to human errors and inconvenient to use, especially for the input of taxonomic data. Therefore, this study focused on developing a system that provides the user an enhanced interface for the generation of the distances of species using their taxonomic data and the computation of the Rao DIVC and DISC. The system features the ability to batch upload spreadsheets as the input sata and save the output to a spreadsheet. Both microsoft Excel and ODS spreadsheets are accepted as input and output formats. Furthermore, the system features a database management system for the taxonomic data and also, the system allows the user to select species from the database and use them for a computation.